Human Factors in Marine Casualties - Švetak, Jelenko (Promet - Traffic&Transportation, 2002)
Human factors play an important role in the origin of accidents,and it is commonly claimed that between seventy andninety-five percent of industrial and transport accidents involvehuman factors, see Figure 1.Some authorities, however, claim that ultimately, all accidentsinvolve human factors.